Structure of PDE3A-SLFN12 complex reveals requirements for activation of SLFN12 RNase - Colin W. Garvie (Nature Portfolio, 2021)
The small molecule DNMDP acts as a velcrin by inducing complex formation between phosphodiesterase PDE3A and SLFN12, which kills cancer cells that express sufficient levels of both proteins. Here, the authors present the cryo-EM structure of the DNMDP-stabilized PDE3A-SLFN12 complex and show that SLFN12 is an RNase. PDE3A binding increases SLFN12 RNase activity, and SLFN12 RNase activity is required for DNMDP-mediated cancer cell killing.